2017
DOI: 10.1111/1744-1633.12282
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of laparoscopic radical prostatectomy and robot‐assisted radical prostatectomy on perioperative, oncological and functional outcomes

Abstract: Aim The aim of the present study was to evaluate the perioperative, oncological and functional outcomes of laparoscopic radical prostatectomy (LRP) and robot‐assisted radical prostatectomy (RARP) performed at our centres. Patients and Methods All LRP and RARP performed from January 2011 to June 2016 were reviewed through electronic patient records. The preoperative cancer characteristics, perioperative parameters, pathology, oncological and functional outcomes were studied. Results A total of 136 men were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The quality assessment of the included non-randomised studies according to the NOS is elucidated in Table S2, Supplemental Digital Content 3, http://links.lww.com/JS9/A366 . It showed that 12 of the 42 included studies had seven stars 35 , 37 , 39 , 44 , 49 , 53 , 57 , 59 , 60 , 63 , 67 , 68 , 20 had eight stars 30 , 32 – 34 , 40 43 , 46 , 48 , 50 52 , 54 , 61 , 62 , 64 , 66 , 69 , 70 , and 10 had nine stars 29 , 31 , 36 , 38 , 45 , 47 , 55 , 56 , 58 , 65 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality assessment of the included non-randomised studies according to the NOS is elucidated in Table S2, Supplemental Digital Content 3, http://links.lww.com/JS9/A366 . It showed that 12 of the 42 included studies had seven stars 35 , 37 , 39 , 44 , 49 , 53 , 57 , 59 , 60 , 63 , 67 , 68 , 20 had eight stars 30 , 32 – 34 , 40 43 , 46 , 48 , 50 52 , 54 , 61 , 62 , 64 , 66 , 69 , 70 , and 10 had nine stars 29 , 31 , 36 , 38 , 45 , 47 , 55 , 56 , 58 , 65 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several previous studies suggested that surgical technique might also affect functional recovery of patients after surgery 31 , 47 , 50 . They believed that compared with LRP, the robotic platforms had the advantages of improved surgical vision and increased precision for preserving of neurovascular structures, which could greatly improve functional recovery after RARP.…”
Section: Discussionmentioning
confidence: 99%
“…b Definition: 0 pad, Yip et al 21 and this paper; 1 pad or less, Lo et al 20 and Cheng et al 22 Abbreviations: NA, not available; PSA, prostate-specific antigen; RALRP, robot-assisted laparoscopic radical prostatectomy.…”
Section: Resultsmentioning
confidence: 99%
“…At the time of this writing, three papers evaluating RALRP in Hong Kong were published. [20][21][22] Concerning the issue as to whether there was any improvement in outcomes throughout the years for RALRP since its first introduction in 2005, the papers by Lo et al 20 and Yip et al 21 covering the early RALRP period (2005 to 2009) were compared with that by Cheng et al 22 and ours covering the later period (2009 to 2017). The various key outcomes were compared and summarized in Table 7.…”
Section: Resultsmentioning
confidence: 99%